The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.aju.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

How practical is the application of percutaneous nephrolithotomy scoring systems? Prospective study comparing Guy’s Stone Score, S.T.O.N.E. score and the Clinical Research Office of the Endourological Society (CROES) nomogram

Abstract: ObjectiveTo prospectively compare the Guy’s Stone Score (GSS), S.T.O.N.E. [stone size (S), tract length (T), obstruction (O), number of involved calices (N), and essence or stone density (E)] score and the Clinical Research Office of the Endourological Society (CROES) nephrolithometric nomogram to predict percutaneous nephrolithotomy (PCNL) success rate and assess the correlation with perioperative complications.Patients and methodsWe prospectively evaluated all consecutive PCNL patients at our institute betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
(87 reference statements)
1
14
1
Order By: Relevance
“…In a large multicentre comparative study, Tailly et al [25] showed that all three scoring systems were equally predictive of post‐PCNL SFS. In a small prospective study cohort, Singla et al [26] performed a similar comparison and drew a similar conclusion. A extensive literature survey showed that Noureldin et al [27] favoured GSS and the STONE score for their significant associations with SFS, whereas Bozkurt et al [28] suggested that GSS and the CROES nomogram were significantly associated with SFS.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In a large multicentre comparative study, Tailly et al [25] showed that all three scoring systems were equally predictive of post‐PCNL SFS. In a small prospective study cohort, Singla et al [26] performed a similar comparison and drew a similar conclusion. A extensive literature survey showed that Noureldin et al [27] favoured GSS and the STONE score for their significant associations with SFS, whereas Bozkurt et al [28] suggested that GSS and the CROES nomogram were significantly associated with SFS.…”
Section: Discussionmentioning
confidence: 63%
“…However, Vicentini et al [35] showed that GSS was associated with post‐PCNL complications. Singla et al [26] found weak correlation of modified Clavien–Dindo grades with the scoring systems.…”
Section: Discussionmentioning
confidence: 99%
“…scores correlated with complications, whereas Tailly et al [18] found that none of them correlated with complications. Tailly et al [18] also found that all three could predict residual fragments and were equivalent; this was also observed by Singla et al [26]. Both of these authors found S.T.O.N.E.…”
Section: Discussionmentioning
confidence: 61%
“…This is higher than that reported by Singla et al ., Shalaby et al ., and Falahatkar et al . at 62.2%, 74.8%, and 76.2%, respectively,[181920] and lower than that reported by Tefekli et al ., 81.6%. [5] Two studies published in 2017 showed identical results regarding stone resolution rates (92%), which is significantly higher when compared to our result.…”
Section: Discussionmentioning
confidence: 68%